Effect of Using Different Levels of Iron with Zinc and Copper in Layer’s Diet on Egg Iron Enrichment - Ramadan , Nehad A.; Omar, Amal S.; Bahakaim, A.S.A.; Osman, Sahar M.H. (International Journal of Poultry Science, 2010)
One hundred and eighty Mandarah laying hens (Egyptian local strain) at 24 wks of age were equally divided into twelve treatments to study the effect of iron, Copper and Zinc supplementation on egg iron concentration, performance and egg quality of laying hens. The experimental treatments included three levels of supplemental iron (Fe) 0, 100 and 200 mg/kg diet, in combination with 0, 20 mg Copper (Cu), 45 mg Zinc (Zn) and 20 mg Cu+45 mg Zn /kg diet in factorial arrangement 3 x 4 during three interval periods (4 weeks each). The highest concentration of egg iron was observed for hens fed diet supplemented with 200 mg Fe/kg in combination with Cu and Zn. Followed by those fed 100 mg Fe/kg with the same previous elements being 3.85 and 3.59 mg/100 gm egg respectively. However, supplementation of Cu and Zn individually without iron gave the lowest values of iron in the egg. Iron supplementation either at the level of 100 or 200 mg/kg improved feed conversion and egg mass. The best value of feed conversion and egg mass was detected for those fed 100 mg Fe/kg with Zn supplementation. Egg quality was not affected by iron supplementation. Zn supplementation resulted in the highest value of shell percentage, while Zn + Cu supplementation showed the best value of Haugh Units. Blood hemoglobin g/100 ml and PCV % increased significantly (p